Effects of maternal captopril treatment during late pregnancy on neonatal lung development in rats - Capelari, Diego Nicolás (2012)
The renin-angiotensin system (RAS) has been implicated in pulmonary hypertension and pulmonary fibrosis. In the present study, we examined the effects of maternal exposure to captopril (2.85. mg/kg/day) during late pregnancy (G13-G21) on postnatal rat lung development. Treatment with captopril during late pregnancy caused a significant decrease in ACE activity in P0 rats. Body weight decreased at P0 (p < 0.001), P8 and P15 (p < 0.01) in captopril-treated rats. Lung weight of P0 and P8 pups was lower in treated-animals (p.< 0.05). Lungs from captopril-treated animals showed impaired alveolar formation, with enlarged distal airway spaces at P8, P15 and P30. Interalveolar wall distance measured by mean linear intercept increased in treated vs. age-matched animals at P8, P15 (p < 0.001) and P30 (p < 0.05) resembling new bronchopulmonary dysplasia. In control animals, the proliferating cell nuclear antigen (PCNA) marker was higher at P0 and then drops gradually, while in captopril-treated animals PCNA marker remains higher at all stages studied. α-Smooth muscle actin (α-SMA), a marker of fibroblast differentiation into myofibroblasts, was higher at the tips of developing secondary septa in captopril-treated lungs at P8 and P15. The increased expression of PCNA and α-SMA in treated pups suggest that beyond the effect caused by captopril, the developing lungs have the capacity to recover once the treatment was stopped. Taking together the low weight, histomorphological changes and increased expression of cellular markers caused by ACE inhibition during late pregnancy, it appears that the RAS could be an intrinsic factor involved in secondary septa formation during lung development.